Analisis Sistem Pengendalian Manajemen terhadap Pemberian Kredit Macet pada Koperasi Simpan Pinjam - Nuri Nurhayati; Dede Rosmiati; Heri Nugraha (COMPETITIVE, 2022)
USP IV KKB IKOPIN is one of the savings and loan units of  Koperasi Keluarga Besar (KKB) which is located in the Jatinangor College Area, Sumedang. There are various types of loans/credits at USP IV KKB IKOPIN, including short-term loans, long-term loans, electronic goods loans and pawn system loans. All these loans/credits are intended to meet the needs of members, namely Lecturers, Employees, Cleaning Services and IKOPIN Students. The research objective to be achieved is to find out how the procedure for granting credit, saving credit and the effectiveness of the bad credit management control system at USP IV KKB IKOPIN using interview research methods to resource persons and collecting cooperative data. From the results of the study, it was found that the effectiveness of control is measured by the application of the 5C principles (character, capacity, collateral, condition of economic and capacity), and USP IV KKB IKOPIN has implemented all of these principles. If there are bad loans, the cooperative will rescue it by rescheduling, namely extending the repayment period, restructuring and confiscation of collateral if there is no good faith and members are unable to repay the loan.Keywords : Sistem pengendalian manajemen pemberian kredit, kredit macet, koperasi simpan pinjam